Designing and rationing a test of measuring the accuracy of the aiming skill by jumping from the corner and some biomechanical variables after performing the physical effort with a handball - Ali , Imad Adel; Neamah Al-Jadaan, Dhurgham A. (International Journal of Psychosocial Rehabilitation, 2020)
The study aims to design a test and standardization to measure the accuracy of the correction skill performance from the corner area of the handball game to identify an indicator of the values of some biomechanical variables of the correction skill for the player. The descriptive method was used in the survey method to solve the research problem. The research sample included some players of the specialized school by hand for the sports season 2019-2020 and the number (54) players. A test is designed to measure the accuracy of the corner correction to be used as a test to assess the performance of players and to obtain accurate results in mechanical analysis. Because we take the successful attempt to extract the biomechanical variables, and the main experiment was conducted to search on the research sample using a video camera and use the (Kinovea-v18) program for skills analysis and data processing using the statistical program SPSS Ver 21. The new test technology has proven its ability to locate defects and invest them in improving performance for scoring from the corner area. The test method reached a set of conclusions, the most important of which are: • Design and codification of a test to measure the accuracy of the angling skill by jumping from a corner and some biomechanical variables after performing the physical effort with a handball. • The highest level achieved by the research sample was at the intermediate level and the lowest level was on average.